Radical cystectomy: do we need standardization?. Issue 2 (1st February 2017) - Ladurner, Christian; Comploj, Evi; Trenti, Emanuela; Palermo, Salvatore; Pycha, Alexander; Pycha, Armin
ABSTRACT: Introduction: The first series of radical cystectomy with a definition of surgical landmarks was published in 1949 and was characterized by a high perioperative mortality and a 5-year survival rate around 50%. Decades later, nevertheless many surgical progresses were made and the perioperative mortality dropped to 2, 5%, this had not lead to an improvement of long term survival rates, also because a standardization of the procedure is still missing. Areas covered: Radical cystectomy is performed with different surgical techniques obmitting a standardization. The comparability of many studies is therefore difficult or havely compromised. A paragon with other diciplines was made emphazing that there high surgical quality is defined, measured and controlled. A systematic literature search was made selecting finally 76 article adressing this issue. Expert commentary: Surgical guidelines in uro-oncology are vague and a definition of surgical quality is missing. A view outside of the box could be very helpful. This is a plea for a change.